EFFICIENCY MODELING OF A SIMPLE LOCAL ELECTRONIC AEROSOLS COLLECTOR FROM GALVANIC BATH - Garshin, V. I.; Geraskova, S. E.; Lebedev, A. R.; Gladkova, D. G. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2017)
The article considers modelling of the simplest elementary link of a local electronic collector of drops of electrolyte, ejected from a galvanic bath in the process of chrome plating of metal parts. Modeling with the use of regression analysis reveals the most significant factors of the technological process and contributes to the development of effective models of above-surface electronic collectors of droplet entrainment and to determination of the optimal ratio between the design parameters and the mode of electronic collection.